Reproduction of Meloidogyne incognita and M. graminis on Several Grain Sorghum Hybrids - Hurd, Katherine (J Nematol, 2017)
A total of 27 grain sorghum hybrids were evaluated in a series of greenhouse experiments to determine their susceptibility to Meloidogyne incognita race 3 and M. graminis. Each hybrid was inoculated with 2,000 nematode eggs/pot. Reproduction by M. incognita was numerically greater than M. graminis on 93% of the hybrids tested, indicating that grain sorghum is a better host for M. incognita than M. graminis. A wide variation in host suitability was observed on these hybrids in a second experiment as reproduction by M. incognita ranged from 395 to 3,818 eggs/g of root. Only two hybrids, Terral RV9782 and RV9823, consistently supported <20% reproduction by M. incognita compared to the most susceptible hybrid, Golden Acres 5556. Reproduction of four isolates of M. incognita was evaluated on six selected hybrids in a third greenhouse experiment. Hybrid susceptibility was similar to that observed in the previous experiment for all isolates. A difference in isolate aggressiveness was observed between two of the four isolates across all hybrids. In fields where damaging populations of M. incognita are present, most grain sorghum hybrids will likely maintain or increase the nematode population for the subsequent crop.